Kalanchoe daigremontiana leaf extract: A green stabilizing agent in synthesis of Silver Nanoparticles (2019)
The synthesis of silver nanoparticles (AgNPs) has been increasingly extended due to its potential applications in fields such as optics, environmental, catalysis, electronics and as an antibacterial agent. In this way it is necessary to develop methods framed in green chemistry to achieve greater stability over time of the AgNPs. The present work aims to show the synthesis of AgNPs using Kalanchoe daigremontiana leaf extract, as a reducing and stabilizing agent. UV-vis and transmission electron microscopy (TEM) were used to characterize AgNPs obtained. The absorbance of solutions was measured, evidencing of the formation of AgNPs due to the existence of plasmon resonance at that ?max ? 417 nm. The size distribution and morphology of the AgNPs by TEM shows stable, spherical and nomodispersar nanoparticles with a size between 4 and 12 nm. The measurements were carried out immediately after the synthesis procedure, then the AgNPs solutions were stored at room temperature and darkness by 27 months and it could be corroborated the stabilizing capacity of Kalanchoe daigremontiana leaf extract, since the ?max and the size of particle did not vary significatively in this period of time. © Published under licence by IOP Publishing Ltd.